ANALYSIS OF CORAL’S COVER AND CORAL’S MORTALITY INDEX AROUND PAGAI STRAIT, MENTAWAI - Herdianan Mutmainah; Rani Santa Clara (AQUASAINS, 2016)
Coral that live in tropical waters that sensitive to environment changes, especially temperature, salinity, sedimentation and eutrophication. Pagai Strait at Mentawai is part of the Indian Ocean which lies between North Pagai and South Pagai Island. Pagai Strait island located in the region which is the path of collision between two plates (Eurasia and Indo-Australia) and high tectonic activities. Some Mentawai Tsunami led severely damaged to most of the Mentawai waters. This study aims to determine of Coral Bleaching phenomenon and the impact of Tsunami, to coral reefs in the Pagai Strait. The method is Line Intercept Transect (LIT) and held in April 2016. The study was conducted on Sijao-jao, Siruso and Tunang Bulag. Observations did on the current, parameters of waters, the percent cover of live coral and dead coral, algae, abiotic and other biota. The result of this research shows that current’s velocity is 0,2 – 0,48 m/sec. Some parameters such as temperature, TDS and salinity out of range of the treshold. pH and visibility are still in the range. Sijao-jao has the percent of coral cover 20,17% (poor) and IM 0,767; Siruso with coral cover 30,45% (moderate) and IM 0,544; while Tunang Bulag has coral cover 25,08% (moderate) and IM 0,451. Acropora sp is the most  vulnerable of coral bleaching.